KARAKTERISTIK MATERI PEMBELAJARAN TAHSINUL QUR'AN BERBASIS NEUROSAINS - Muh. Fathul Mubin (Edusoshum : Journal of Islamic Education and Social Humanities, 2021)
The learning of taḥsinul Qur’ān to enable Muslims to read the Qur’ān with tarteel has still become a challenge in Indonesia. Its factors include the complexity and complicatedness of makhārijul huruf and Arabic sounds’ characteristics. This qualitative research aims at explaining forms of material delivery and material components in books for taḥsinul Qur’ān learning. Its data were from nine books used as public as well as restricted learning resources. The content analysis was applied using neuroscience, especially related to the characteristics of learning materials, which might be boring or enjoyable and difficult or easy based on the brain functions. Findings show that 1) There are eight forms of material delivery: theory, examples, excercises, pictures, encoding-decoding, diagram, summary, and evaluation. Only one book has all eight forms. Examples and exercises appear in all books, encoding-decoding and evaluation in four books while pictures and summary in  three books; 2) The learning materials consist of  four components: learning guidelines, guidance for reciting the Qur’ān,  hijaiyah sounds, and Ibtida’ and Waqaf.  Only three books contain all components. Variation of forms in material delivery makes the materials enjoyable and easy for learners. Sufficient material components are also important to support effective taḥsinul Qur’ān learning.